The role of ILC2 in hookworm infection. (22nd May 2017) - Filbey, K.; Bouchery, T.; Le Gros, G.
Summary: Hookworm is a major public health concern, yet still relatively little is known about the immunological responses involved in human infection. Animal studies are mainly confined to using the natural rodent helminth Nippostrongylus brasiliensis as this has been proposed as the most accurate model of hookworm infection in the mouse, with both its life cycle and the immune responses it invokes having been extremely well characterized. In this review, we examine the roles that type 2 innate lymphoid cells (ILC2s) play in immunity and host tolerance to hookworm infection, particularly N. brasiliensis . This includes their role in the initiation and regulation of immune responses, as well as in the resolution and limitation of tissue damage required after an infection with a large organism, such as a helminth.